Pengaruh Rasio Keuangan Terhadap Harga Saham Syariah pada Akr Corporindo - Maryam Batubara; Syafrina Yuni Lubis; Patma wati (Institut Muslim Cendekia, 2023)
The share price is the price of a share on the ongoing market on the stock exchange which is formed through a supply and demand mechanism in the capital market. Fluctuations that occur in stock prices at PT. AKR Corporindo caused the financial condition or fundamentals of the company to not be good. Where are the factors that influence stock prices, namely Earning per Share, Debt Equity Ratio and Book Value per Share.This research is a quantitative research with data analysis using SPSS version 22. This study concluded there is an effect of Earning Per Share (EPS) on share prices partially, there is no effect of Debt To Equity Ratio (DER) on share prices partially, , there is no effect on Book Value Per Share (BVS) on share prices partially and there is the influence of Debt To Equity Ratio, Earning Per Share and Book Value Per Share simultaneously on stock prices simultaneously at PT. Akr Corporindo Tbk 2014-2021